SANCTIONS EVASION AND VIRTUAL ASSETS: IMPLICATIONS FOR NATIONAL SECURITY - VACUSTA, Bogdan (Strategic Impact, 2023)
2022 was the year marking a significant increase in the use of virtual assets for illicit activities such as sanctions evasion. Most of the entities conducting these activities are linked to Russia, North Korea and Iran, which are subject to international sanctions imposed by the international community. The paper presents key elements about the use of virtual assets in illicit activities by sanctioned entities and highlights the necessity to increase defence and intelligence resources for better data analysis on this type of entities. Analyzing data about virtual assets transactions requires strong collaboration between public and private organizations, with a focus on an intelligence-led approach, considering the growing links between cybercrime, money laundering, terrorist financing, special operations conducted by adversaries. In order to support this collaboration, it is essential to prioritize the education of decision-makers on the necessity to focus on technical data.